The use of occlusive dressings: influence on excisional wound healing in animal model - Mariana Raquel Soares Guillen; Eline Lima Borges; Gilmara Lopes Amorim; Puebla Cassini Vieira; Antônio Carlos Martins Guedes; Luciola Silva Barcelos (Acta Cirúrgica Brasileira, 2023)
ABSTRACT Purpose: To analyze the influence of occlusive dressing on the healing of excisional skin wounds in mice. Methods: Pre-clinical, comparative, and translational study. Mice were divided into three experimental groups: wounds occluded with hydrocolloid (HD) dressings, transparent polyurethane film (TF) dressings, and without occlusion (WO), monitored at three, six and 14 days, with eight animals each. Closure rate, infiltration of neutrophils and macrophages, measurement of tumor necrosis factor-α (TNF-α) and vascular endothelial growth factor (VEGF) and, histologically, angiogenesis were evaluated. Results: Wound closure was accelerated in the occlusive groups. There was a decrease in TNF-α levels in the HD group when compared to the WO and TF groups. Neutrophils accumulation decreased in the HD group. Increased dosages of macrophages were evidenced in the HD group, compared to the WO and TF groups. Levels of VEGF were increased in the TF and HD groups. Conclusions: It is suggested that the occlusion of wounds modulates the inflammatory response.